Relationship between Age and The Histopathological Features to Chemotherapy Response in Colorectal Cancer Patients: A Prospective Observational Study - Lukman, Kiki; Gunawan, Gun Gun; Rudiman, Reno; Sribudiani, Yunia; Hasibuan, Lisa Y.; Dewayani, Birgitta M.; Nugraha, Prapanca; Primastari, Etis (Journal of Coloproctology, 2023)
Introduction Chemotherapy response in early age-onset colorectal cancer patients is still controversial, and the results of chemotherapy response are unknown. Therefore, the purpose of this study is to determine the relationship between the age of colorectal cancer patients and histopathological features and chemotherapy response.Methods This is a prospective observational study. The subjects in this study were colorectal cancer patients in the Digestive Surgery division at Tertiary Hospital in West Java from September 2021 to September 2022.Results There were 86 subjects who underwent chemotherapy in accordance with the inclusion and exclusion criteria. Consisting of 39 patients of early age onset and 44 female patients. The most common histopathological feature in early age onset (EAO) and late age onset (LAO) was adenocarcinoma (25% and 46%, respectively). Stage III colorectal cancer affected 38 patients, while stage IV affected 48 patients. There was a significant relationship between early age onset and late age onset with histological features (p < 0.001). The patients with the highest chemotherapy response had stable diseases in EAO (17 patients) and LAO (20 patients). There was no statistically significant relationship between age, histological features, and stage of colorectal cancer and chemotherapy response (p > 0.05). The results of the ordinal logistic regression test showed no systematic relationship between chemotherapy response and age, histopathological features, gender, or cancer stage (p > 0.05).Conclusion There was no association between age and histopathologic features with chemotherapy response and there is no difference in chemotherapy response between early and late age onset.
Keywords: early-onset; chemotherapy; histopathological features; late-onset